MODERN APPROACHES TO THERAPY OF UROGENITAL DISORDERS IN POST-MENOPAUSAL FEMALES - T. S. Perepanova; P. L. Khazan (Акушерство, гинекология и репродукция)
Pathogenesis of isolated urogenital disorders in post-menopausal females is often rooted in reduced production of female sex hormones. As a rule, such disorders are not related to infectious diseases. Therefore, the main objective of therapy of postmenopausal urogenital disorders is to supplement the deficiency of female sex hormones. Topical administration of therapeutic doses of estriol as a cream or Ovestin suppositoria, is recognized as one of the safest methods of treatment. Upon completion of the treatment course, which duration is 3 weeks, a switching to maintenance therapy is indicated.